A conspiracy of paper a novel - Liss, David 1966- (New York The Random House Publishing Group, 2001)
"Benjamin Weaver, a Jew and an ex-boxer, is an outsider in eighteenth-century London, tracking down debtors and felons for aristocratic clients.The son of a wealthy stock trader, he lives estranged from his family--until he is asked to investigate his father's sudden death. Thus Weaver descends into the deceptive world of the English stock jobbers, gliding between coffee houses and gaming houses, drawing rooms and bordellos. The more Weaver uncovers, the darker the truth becomes, until he realizes that he is following too closely in his father's footsteps--and they just might lead him to his own grave."--Back cover.
"A Ballantine book."
"A New York Times notable book"--Cover.
Includes reader's guide (pages [443-455])
"February 2001"--Title page verso.
Originally published: New York : Random House, ©2000.